Behavioral Thermal Modeling for Microwave Power Amplifier Design - Mazeau, J.; Sommet, R.; Caban-Chastas, D.; Gatard, E.; Quere, R.; Mancuso, Y. (IEEE transactions on microwave theory and techniques, 2007)
System-level models simplify the analysis of complex RF systems, such as transmission-reception modules, by expressing global input-output relationships. However, the development of high RF power models for nonlinear subsystems requires the prediction of the distortion induced by low-frequency memory effects such as self-heating effects. In this framework, we present a new electrothermal behavioral model for power amplifiers. This global model is based on the coupling between a behavioral electrical model derived from the transistor-level description of the amplifier and a thermal reduced model. This model, implemented into a circuit simulator, allows to predict the impact of the thermal effects in pulsed RF mode thanks to an envelope transient analysis. This approach has also been validated by measurements.